TO THE QUESTION OF THE ALIGNMENT OF THE RAILWAY TRACK WITH ITS REPAIRS - Yershova, K. B.; Petukhovskyi, V. V.; Petukhovskyi, S. V.; Kholin, O. Ye.; Yudin, B. O. (Science and Transport Progress, 2006)
Questions concerning various methods of lining of a track are stated, the comparative analysis of results of work of systems of lining of a track (ALC, «Navigator», MS VNIIZHT-MATESS) is resulted, prospects of use of a method of calculation of spatial position of a track realized in MS VNIIZHT-MATESS.